Poverty in rural forest communities and its management: a case study in Malinau District - Rositah, E. (Center for International Forestry Research, 2006)
Does the local government’s increased access to forest resources in the district have an impact upon poverty? Regional autonomy provides district governments with the authority to improve the welfare of communities in their districts. Malinau District in East Kalimantan has the opportunity to develop the livelihoods of its communities. Even though it has abundant natural resources, Malinau has yet to be able to guarantee a better standard of living for the majority of its people. The population of the district at the end of 2003 was around 43,844 spread across nine subdistricts, with the majority living in remote villages in or around forests. In the same year approximately 47% of households or families were recorded as being poor (Malinau District Rural Community Empowerment Office, 2003). The aim of this case study paper is to look at the impact of regional autonomy on two poor communities in this wealthy district, i.e. Sebinuang (North Malinau Subdistrict) and Metut (South Malinau Subdistrict).